Desempenho dos alunos no Enade: uma comparação por meio do capital cultural entre as modalidades presencial e o EAD - Baldissera, Patricia (2016)
In the last decade, the expansion of Distance Education has acquired large proportions in Brazil and worldwide. This growth has allowed the democratization of access to education, making it a key tool for promoting opportunities for many individuals. However, the expansion of Higher Education through the Distance mode puts into question the quality of these new courses. Would they have the same standards and qualitative results as the presencial ones? Considering the ongoing expansion and the issue of quality, knowing the specifics of Distance Education mode becomes increasingly important to promote actions for its management in the pursuit of educational quality. To this end, this research seeks in its main objective to contribute to the construction of knowledge about the quality of Distance Education in Brazilian Higher Education. The research is characterized as quantitative of applied nature. The investigations will be carried out by comparing the performance of undergraduate students in ENADE tests taken in the years 2005, 2006, 2007, 2008, 2009 and 2010. Data from INEP micro data will be submitted to an analysis work through statistical software, taking as reference the international literature on school effectiveness in Higher Education. The analysis of the calculations on student performance will be carried out especially on excluding influences of background on student performance and will be based on the theoretical perspectives of Pierre Bourdieu on the cultural capital. At the end of the investigations, some considerations will be drawn, searching for answer the starting question of this project on the difference of performance between the EAD and Presencial modes.